2011
DOI: 10.1212/wnl.0b013e3182242d4d
|View full text |Cite
|
Sign up to set email alerts
|

Recessive axonal Charcot-Marie-Tooth disease due to compound heterozygous mitofusin 2 mutations

Abstract: Our findings confirm that MFN2 mutations can cause early-onset CMT2 with apparent recessive inheritance. Novel genetic findings include an intragenic MFN2 deletion and nonsense-mediated decay. Carrier parents were asymptomatic, suggesting that MFN2 null alleles can be nonpathogenic unless coinherited with another mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 14 publications
3
55
0
Order By: Relevance
“…Toxic gain-of-function, rather than haploinsufficiency, may be responsible for dominant inheritance in CMT2A [89]. In support of this hypothesis, deletion of one MFN2 allele in mice is asymptomatic, as are truncating MFN2 mutations in humans, unless inherited in conjunction with an additional mutation in MFN2 or another CMT-associated allele [1011]. …”
Section: Introductionmentioning
confidence: 99%
“…Toxic gain-of-function, rather than haploinsufficiency, may be responsible for dominant inheritance in CMT2A [89]. In support of this hypothesis, deletion of one MFN2 allele in mice is asymptomatic, as are truncating MFN2 mutations in humans, unless inherited in conjunction with an additional mutation in MFN2 or another CMT-associated allele [1011]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gain of function experiments in mice overexpressing a CMT-linked mutant MFN2 allele, demonstrated that this was sufficient to induce a specific neurological phenotype [7]. Despite this, several CMT patients with compound heterozygote MFN2 mutations have been reported, and these all manifested as recessively inherited CMT2A [8]. Thus it is feasible that mutant MFN2 can cause CMT in both a dominant and a recessive fashion, depending on the specific genetic defect.…”
Section: Introductionmentioning
confidence: 99%
“…Other compound heterozygous mutations, p.G108R and p.R707W, were reported in three siblings by Calvo et al (20) where the parents had no signs of peripheral neuropathy, had normal electrophysiological findings and each carried a single heterozygous mutation. Polke et al (27) reported three patients with recessive mutations. In two siblings the combination of missense mutations and deletion of 2 exons was observed.…”
Section: Discussionmentioning
confidence: 99%